2015
DOI: 10.1371/journal.pone.0126114
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Relationships of Meso-Scale Distribution in 25 Neotropical Vertebrate Species

Abstract: Vertebrates are a vital ecological component of Amazon forest biodiversity. Although vertebrates are a functionally important part of various ecosystem services they continue to be threatened by anthropogenic impacts throughout the Amazon. Here we use a standardized, regularly spaced arrangement of camera traps within 25km2 to provide a baseline assessment of vertebrate species diversity in a sustainable use protected area in the eastern Brazilian Amazon. We examined seasonal differences in the per species enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 64 publications
5
42
0
1
Order By: Relevance
“…In this study Carnivora was the most speciose order, followed by Artiodactyla, in both PAs and IAs, suggesting that the structure of the mammalian community is preserved, although some of the species are generalist and matrix/fragmented tolerant species, such as Eira barbara. Studies in the Neotropics have shown that Carnivora is the most speciose order of large terrestrial mammals in protected areas, followed by Artiodactyla (Tobler et al 2008, Munari et al 2011, Springer et al 2012, Santos and Oliveira 2012, Ahumada et al 2013, Burton et al 2015, Michalski et al 2015, whereas in protected areas that are surrounded by human disturbances, Carnivora was followed by Rodentia and Xenarthra, which could represent an intermediate conservation status (Pickles et al 2011, Carvalho et al 2014, Lizcano et al 2016, or Rodentia could even be the most speciose order (Michalski et al 2015). In impacted areas, however, the most speciose order seems to be Xenarthra, followed by Rodentia Peres 2007, Botelho et al 2012).…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study Carnivora was the most speciose order, followed by Artiodactyla, in both PAs and IAs, suggesting that the structure of the mammalian community is preserved, although some of the species are generalist and matrix/fragmented tolerant species, such as Eira barbara. Studies in the Neotropics have shown that Carnivora is the most speciose order of large terrestrial mammals in protected areas, followed by Artiodactyla (Tobler et al 2008, Munari et al 2011, Springer et al 2012, Santos and Oliveira 2012, Ahumada et al 2013, Burton et al 2015, Michalski et al 2015, whereas in protected areas that are surrounded by human disturbances, Carnivora was followed by Rodentia and Xenarthra, which could represent an intermediate conservation status (Pickles et al 2011, Carvalho et al 2014, Lizcano et al 2016, or Rodentia could even be the most speciose order (Michalski et al 2015). In impacted areas, however, the most speciose order seems to be Xenarthra, followed by Rodentia Peres 2007, Botelho et al 2012).…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 99%
“…Different patterns, however, may be found in highly impacted areas, in which most medium-sized and large mammals are extirpated or driven to such low numbers that the most abundant species becomes the smallerbodied rodent, Dasyprocta spp. (Tobler et al 2008, Botelho et al 2012, Michalski et al 2015, Lizcano et al 2016.…”
Section: Determinants Of the Structure Of The Mammalian Assemblagesmentioning
confidence: 99%
See 3 more Smart Citations